2001
DOI: 10.2337/diabetes.50.12.2673
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Pre- and Postsynaptic Influences on Glucosensing Neurons in the Ventromedial Hypothalamic Nucleus

Abstract: Glucosensing neurons in the ventromedial hypothalamic nucleus (VMN) were studied using visually guided slicepatch recording techniques in brain slices from 14-to 21-day-old male Sprague-Dawley rats. Whole-cell current-clamp recordings were made as extracellular glucose levels were increased (from 2.5 to 5 or 10 mmol/l) or decreased (from 2.5 to 0.1 mmol/l). Using these physiological conditions to define glucosensing neurons, two subtypes of VMN glucosensing neurons were directly responsive to alterations in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
387
5
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(412 citation statements)
references
References 32 publications
16
387
5
2
Order By: Relevance
“…The PVN is known to contain GR neurons, while the ARC contains both GS [19] and GR [30] neurons. The ventral hypothalamus segment also incorporated the VMN, which contains both GR, and somewhat fewer, GS neurons [15]. In line with previous studies [26] increased basal NPY overflow was observed in both the dorsal and ventral hypothalamus as a result of treatment with STZ, and the increase was greater in the dorsal area.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The PVN is known to contain GR neurons, while the ARC contains both GS [19] and GR [30] neurons. The ventral hypothalamus segment also incorporated the VMN, which contains both GR, and somewhat fewer, GS neurons [15]. In line with previous studies [26] increased basal NPY overflow was observed in both the dorsal and ventral hypothalamus as a result of treatment with STZ, and the increase was greater in the dorsal area.…”
Section: Discussionsupporting
confidence: 91%
“…Glucose sensing in the central nervous system (CNS) has been associated with the glucose sensing neurons [13]. Clear evidence of abnormalities in central glucose sensing and transport have been shown in Type I diabetes, involving a resetting of the normal homeostatic mechanisms [14], and more recently in diet-induced obesity [15].…”
mentioning
confidence: 99%
“…In the ventromedial hypothalamus (VMH), a majority of responding neurons increased their firing rate (glucose-responsive or glucose-stimulated), whereas in the lateral hypothalamus (LH), a majority reduced their activity (glucose-sensitive or glucose-inhibited). These results have been elegantly confirmed and extended by more recent studies, for example [142,145]. Several reports and experiments on K IR 6.2KO mice (98; see 28, 86, 125 for review) indicate that glucose-stimulated neurons in the VMH underlie the counterregulatory response to hypoglycemia, although Yang et al [155] have reported that glucose-inhibited neurons are involved.…”
Section: Acetylcholine and Amino Acidsmentioning
confidence: 65%
“…The right panel illustrates three potential mechanisms whereby glucose metabolism is hypothesized to hyperpolarize glucose-inhibited neurons and decrease their firing rate. Song et al [145] have suggested metabolic activation of an inward chloride (Cl − ) flux would result in hyperpolarization as diagramed in the lower left side of the right panel. Following the astrocyte-neuron lactate shuttle model [33,76,115] and Lam et al [83], glucose metabolism in astrocytes leads to shuttling of lactate (Lac) into neurons via monocarboxylate transporters (MCTs), where it is converted to pyruvate (Pyr) and metabolized in mitochondria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation